Роль інтеграційних стратегій у розширенні бізнесу та створенні ланцюгів вартості - Миськів, Г. В.; Тагієв, Є. А.; Myskiv, G. V.; Tahiyev, Ye. A. (Видавництво Львівської політехніки, 2024)
У статті досліджено сутність та види інтеграційних стратегій, що використовують підприємства для досягнення конкурентних переваг з метою розширення бізнесу та збіль- шення ринкової частки. З точки зору теоретичного аналізу, розглянуто та систематизо- вано основні характеристики вертикальної, горизонтальної та конгломератної інтеграції. Особливу увагу приділено перевагам і недолікам означених інтеграційних стратегій, а та- кож сучасним умовам, які спонукають компанії до прийняття рішень про інтеграцію. Практичні аспекти розширення бізнесу через інтеграцію показують, як такі стратегії сприяють оптимізації ресурсів, зниженню витрат і покращенню якості продуктів та по- слуг. Підкреслено важливість адаптації підприємств до динамічного бізнес-середовища та необхідність ефективного управління інтеграційними процесами для створення стійких ланцюгів вартості. Автори доходять висновку, що стратегічна інтеграція процесів, систем і функцій буде залишатися основою сталого зростання та успіху підприємств на ринку, зважаючи на постійний розвиток бізнес-ландшафту.

The contemporary business landscape is marked by high dynamismand intense competition, compelling businesses to seek novel strategies to achieve success. Integration strategies, which involve the amalgamation of resources and competencies fromdifferent companies to achieve shared goals, constitute a crucial tool in this pursuit. The objective of this study is to delve into the role of integration strategies in business expansion and value chain creation. It scrutinizes the advantages and disadvantages of integration strategies, emphasizing the contemporary factors that drive businesses toward integration decisions, such as heightened competition and globalization, a dynamic business environment, technological advancements, and rapid innovation. The study identifies three types of integration strategies: vertical (combining different stages of the production process), horizontal (merging companies at the same level of the production chain), and conglomerate (integrating businesses from diverse sectors into a single structure). It explores the feasibility of realizing these strategies through mergers, acquisitions, or takeovers. The research highlights the key benefits and drawbacks of integration strategies. Advantages include increased market share and strengthened competitive edge, cost reduction through efficient resource utilization, expanded access to new markets and customers, access to new technologies and innovations, and optimized supply chains and logistics. However, the article also acknowledges potential disadvantages associated with integration, such as risks of conflict of interest among companies, challenges in managing large and complex organizations, high integration costs, reduced flexibility and adaptability to change, employee conflicts, and potential redundancies due to overlapping functions. As a result, the article underscores the relevance of integration strategies in contemporary business and offers practical recommendations for their effective utilization to achieve a competitive edge and establish resilient value chains. While any integration strategy can potentially be successful, companiesmust first clearly identify the production processes that would most significantly impact their profitability if dramatically improved. This understanding serves as a crucial foundation before implementing any specific integration strategy.
The impact of integration strategies on business growth and value chain development
Keywords: інтеграційні стратегії; горизонтальна інтеграція; вертикальна інте- грація; конгломератна інтеграція; ринкова частка; створення ланцюга вартості; конку- рентна перевага; integration strategies; horizontal integration; vertical integration; conglomerate integration; market share; value chain creation; competitive advantage; 330.322; 658.14